(untitled) (Journal of NELTA, 2018)
Teaching English without any instructional materials may be difficult or even impossible. There are lots of materials which facilitate both the teachers and students in language teaching and learning. As with other teaching materials and resources, journal articles are also an important source for language teaching. Taking this into account, this article tries to explore how EFL teachers perceive the value of journal articles and how they use them in their classrooms. More specifically, the article tries to explore whether and to what extent journal articles can be used as instructional materials, and what strategies teachers employ to use journals articles to enhance language proficiency of their students. Journal of NELTA , Vol. 22, No. 1-2, 2017 December, Page: 110-116